Variability of the nurses educators' judgement on the learning problems and teaching strategies: results from a preliminary study. - Fachin M; Tomietto M; Valoppi G; Palese A (International Nursing Perspectives)
Introduction. In their daily practice, the nurse educators recognize the students' learning problems and they decide the most effectiveness learning strategy in order to help/sustain the student in his/her learning process. When the nurse educator takes these decisions, he/she doesn't have particular support (e.g. instruments for standardizing learning problems diagnosis, evidence base guidelines for deciding effectiveness tutorial strategies) if compared with clinical nurses which have taxonomies and professional guidelines. The aim of this paper is to describe how the nurse educators nominate the nursing students learning problems, and the variability of teaching strategies that they decide. Only through the analysis of the nurse educators' practice is possible to develop the tacit knowledge already available in the Nursing Bachelor Courses.Methods. The aim of the study was to describe the variability of the nurse educators' judgment when they made decisions for students with clinical learning problems. A quantitative-qualitative research method was adopted. Nurse educator from three Nursing Bachelor Courses were involved in Friuli Venezia Giulia region (Udine, Pordedone, Trieste). A scenario describing a nursing student with clinical learning problems was created. The participants involved were asked to analyse this scenario and to respond to two main questions: What is the learning problem of this student? What is the best strategy for help the student in overcoming the problem that you have diagnosed?Results. 23 nurse educators were involved. For the same scenario, they recognized 8 different learning problems (ranging from 'lack of awareness about the educational level requested by the school'; to 'demotivation'; or 'lack of ability to transfer the acquired knowledge in the practice'). The Nurse Educators have described, for the same scenario, 12 different teaching strategies.Discussion. Within the limits of the study, the need to have sharing moments in the School of Nursing in order to discuss learning problems of the students and the best teaching strategies are emerged. It would interesting to develop a learning problems taxonomy and a coherent set of strategies. Only reducing the variability in the nurse educator judgement is possible to develop research projects aiming to evaluate the effectiveness of the teaching strategies.